Reconstructing zakat within sharia philanthropy - Pertiwi, Hana Pertiwi,; Atika, Atika; Abdillah, Muhammad (Journal of Islamic Economics Management and Business (JIEMB), 2023)
The quality of a believer’s faith in Islam is evidenced through their interactions in a social context, with zakat being a critical religious duty that transcends mere ritualistic worship to embody profound social implications. This study explores the reconstruction of zakat within Sharia philanthropy to enhance its effectiveness in alleviating poverty and supporting sustainable welfare. Using a qualitative descriptive approach, the research involves an extensive literature review and data analysis from various sources. Findings indicate that zakat, when managed properly, significantly improves the economic well-being of the ummah, particularly among the poor and the eight designated beneficiaries. The article identifies critical factors facilitating zakat reconstruction, such as legal frameworks, community engagement, and technological advancements. It also highlights the challenges in zakat management, including regulatory issues and inefficiencies in distribution. The implications of reconstructing zakat within Sharia philanthropy include enhanced transparency, efficiency, and impact on social welfare, transforming recipients from passive beneficiaries into active, productive community members. This article contributes to the discourse on Islamic social finance by proposing a structured approach to optimizing zakat practices, thereby aligning them with the aspirations of the Muslim community for equitable economic development.